Planetary scale climatic change through bioengineering the microbial world. A technofix imaginary - Fulvi, Daniele; Wodak, Josh (Futures : the journal of policy, planning and futures studies, 2024)
This article critically analyses the imaginary that is emerging from attempts to mitigate planetary scale climatic change through bioengineering the microbial world, that is, through synthetic biology. We explore how engineering microbial life is put forth by its advocates as a viable means of mitigating climate change and thus conferring benefit for future human and more-than-human life. We discuss how these promises, while far-reaching, translate into a technofix imaginary, whereby a future existence of human and untold more-than-human life is contingent on the realisation of such promises. Moreover, we illustrate how the engineering imaginary of synthetic biology is not limited to life alone, but is rather the byproduct of an aspiration to control global ecosystems and climates, and even the course of evolution, via the manufacturing and control of life at the microbial level. We conclude with a critique of how such an imaginary remains incommensurate with fundamental aspects of life that elude human control, and will arguably continue to do so. Thus, the technofix imaginary of synthetic biology is likely to be scaled down in order to reflect the actual achievements of the field, and not its speculative applications. •Synthetic biology relies on promises to tackle planetary issues such as climate change by bioengineering microbial life.•These promises translate into a technofix imaginary, whereby the future of life on Earth is contingent on their realisation.•This imaginary stems from a total engineering paradigm, aimed at controlling global ecosystems, climates, and evolution.•However, microbial lifeforms have traditionally eluded human attempts to control, and will arguably continue to do so.•The imaginary of synthetic biology is likely to be scaled down to reflect the actual achievements of the field.